Cohesin Core Complex Gene Dosage Contributes to Germinal Center Derived Lymphoma Phenotypes and Outcomes - Rivas, Martin A.; Durmaz, Ceyda; Kloetgen, Andreas; Chin, Cristopher R.; Chen, Zhengming; Bhinder, Bhavneet; Koren, Amnon; Viny, Aaron D.; Scharer, Christopher D.; Boss, Jeremy M.; Elemento, Olivier; Mason, Christopher E.; et al. (Frontiers in Immunology, 2021)
The cohesin complex plays critical roles in genomic stability and gene expression through effects on 3D architecture. Cohesin core subunit genes are mutated across a wide cross-section of cancers, but not in germinal center (GC) derived lymphomas. In spite of this, haploinsufficiency of cohesin ATPase subunit Smc3 was shown to contribute to malignant transformation of GC B-cells in mice. Herein we explored potential mechanisms and clinical relevance of Smc3 deficiency in GC lymphomagenesis. Transcriptional profiling of Smc3 haploinsufficient murine lymphomas revealed downregulation of genes repressed by loss of epigenetic tumor suppressors Tet2 and Kmt2d. Profiling 3D chromosomal interactions in lymphomas revealed impaired enhancer-promoter interactions affecting genes like Tet2, which was aberrantly downregulated in Smc3 deficient lymphomas. Tet2 plays important roles in B-cell exit from the GC reaction, and single cell RNA-seq profiles and phenotypic trajectory analysis in Smc3 mutant mice revealed a specific defect in commitment to the final steps of plasma cell differentiation. Although Smc3 deficiency resulted in structural abnormalities in GC B-cells, there was no increase of somatic mutations or structural variants in Smc3 haploinsufficient lymphomas, suggesting that cohesin deficiency largely induces lymphomas through disruption of enhancer-promoter interactions of terminal differentiation and tumor suppressor genes. Strikingly, the presence of the Smc3 haploinsufficient GC B-cell transcriptional signature in human patients with GC-derived diffuse large B-cell lymphoma (DLBCL) was linked to inferior clinical outcome and low expression of cohesin core subunits. Reciprocally, reduced expression of cohesin subunits was an independent risk factor for worse survival int DLBCL patient cohorts. Collectively, the data suggest that Smc3 functions as a bona fide tumor suppressor for lymphomas through non-genetic mechanisms, and drives disease by disrupting the commitment of GC B-cells to the plasma cell fate.